Analisis Kegiatan Pengabdian Masyarakat Dalam Penerapan Pembukuan Sederhana Bagi UMKM - Erni Wahyuni; Rika Syahmewah Munthe; Amron Zarkasih; Irhamna Mandili (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
Micro, small and medium enterprises (MSMEs) generally have not carried out financial management, especially simple bookkeeping. The lack of knowledge and capacity of resources is a contributing factor. The preparation of this article aims to analyze community service in the application of simple bookkeeping for MSMEs. The analysis was carried out with a brief review of the publications of related community service activities over the last 5 years. The results of the review were analyzed from the aspect of activity methods, activity results and constraints or recommended suggestions. The results of the analysis show that many training and mentoring methods are used to obtain consistency and continuity. The lack of financial management knowledge can be overcome by education on the importance of bookkeeping. A simple digital-based bookkeeping application is highly recommended because of the effectiveness and efficiency factor.